Estudio y diseño eléctrico para el cambio de la matriz energética de la autogeneración a la conexión de la red eléctrica pública, utilizando un analizador de redes eléctricas AEMC 8335 en la cantera Luzagui. - Granizo Ruiz, Hernán Fabrizio (2019)
Alternatives and prospects for development of Ecuador's present energy system. Conducting an analysis of the current energy matrix and the possibilities of improving highlighting, in particular, hydropower, because of the importance of the supply of the energy demands of the country. This work will allow development for the change of the energy matrix for self-transformation in the connection of the mains at the quarry Luzagui, using a network Analyzer electrical AEMC 8335, which will identify the technical values Electric for the correct implementation of the change of energy matrix. The study cost-benefit allows a check of whether it is feasible to change the current energy matrix. When comparing current expenditures by generation to the connection from the public mains supplied provided by CNEL, in addition, the technical requirements for the presentation of an electrical project to the electricity distribution company are specified for its implementation in the quarry, where production costs would be minimized.